PELATIHAN PENYUSUNAN PENELITIAN TINDAKAN KELAS (PTK) DAN ANALISIS DATA BAGI GURU SD - Farida, Nur; Suwanti, Vivi (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
Abstract: The purpose of this service is to provide insight and training in the production of CAR. KKG is a place for teachers to collaborate and gather to explore learning done in schools. Teacher Working Groups (TWG) have an important role in supporting the development of teacher professionalism. To realize the role of the Teacher Working Group (TWGG) in developing teacher professionalism, the method offered to resolve partner problems is a Workshop related to the preparation of classroom action research (CAR) throughout Singosari District. To train skills in the production of CAR, training and mentoring of teacher groups will be carried out in the form of CAR. In this activity, a teacher group was assisted in the preparation of CAR, data analysis and introduction of CAR mathematics software.Based on interviews with teachers at Pagentan 1 Singosari Elementary School there are several problems, namely 1) Lack of understanding of CAR, 2) Ability to make CAR is still lacking, and 3) Lack of understanding of mathematical software. The solution offered is to provide CAR education for elementary school teachers, provide training in the production of CAR in elementary schools, and the introduction of mathematical software for learning for learning aimed at the process of analyzing outcome data. This activity resulted in an increase in understanding of elementary school teachers in the production of CAR so that it could improve teacher competency in learning and analyze CAR results from statistical data through mathematical software.